Effectiveness and Safety Profile of Short-Term NSAIDs Protocols in Dental Implantology. A Systematic Review of Clinical Evidence - Bueso-Ruiz, Mario; Montero-Aguilar, Mauricio; Esparza-Villalpando, Vicente; Pozos-Guillén, Amaury; Chavarría-Bolaños, Daniel (Odovtos - International Journal of Dental Sciences, 2025)
This systematic review aimed to assess the clinical effectiveness and biological safety of short-term non-steroidal anti-inflammatory drugs (NSAIDs) in managing postoperative pain following dental implant surgery. A comprehensive literature search was conducted across eight databases through March 2023, following PRISMA guidelines. Only randomized controlled trials (RCTs) evaluating short-term (≤7 days) NSAID use in patients undergoing dental implant placement were included. Outcomes assessed included postoperative pain, swelling, need for rescue medication, patient satisfaction, adverse events, and effects on osseointegration. Risk of bias was assessed using GRADE and OCEMB tools. Ten RCTs met the inclusion criteria. NSAIDs studied included ibuprofen, naproxen, meloxicam, piroxicam, lornoxicam, dexketoprofen, and diclofenac. Most studies reported reduced postoperative pain and lower need for rescue medication with NSAIDs compared to placebo. Several trials also found higher patient satisfaction and reduced swelling. No significant adverse effects on marginal bone loss or osseointegration were observed in the short term. Risk of bias varied: three studies were low risk, four had some concerns, and three had high risk due to inadequate blinding or unclear randomization.The short-term use of NSAIDs appears to be effective in reducing postoperative pain and swelling after dental implant placement without negatively affecting osseointegration. However, heterogeneity in study design, protocols, and outcomes prevented meta-analysis. Further high-quality RCTs with standardized protocols are needed to establish clear clinical guidelines.